Gillian Flynn’s Small Town Crime Fiction - Antoine Dechêne (Belphégor)
This paper addresses the profound sense of place in Gillian Flynn's crime fiction, which transpires through the locale of the small town. Distinguishing between setting and landscape, the analyses of Sharp Objects, Dark Places, and Gone Girl reveal a tendency in the genre towards more realistic and social narratives which blend melancholic atmospheres and characters into complex storyworlds highlighted with metaphysical overtones. The article's overall claim is that Flynn's crime fiction has an important social dimension reminiscent of the hard-boiled. Her novels indeed explore new avenues of a form of rural hard-boiled in which there are no tough guys or super villains, but rather ordinary men and women who struggle with their own epistemological and ontological limitations.